Optimum Growth when Capital is Non-transferable - Dasgupta, P. S. (Review of Economic Studies, 1969)
Journal Article Optimum Growth when Capital is Non-transferable Get access P. S. Dasgupta P. S. Dasgupta Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 36, Issue 1, January 1969, Pages 77–88, https://doi.org/10.2307/2296344 Published: 01 January 1969 Article history Received: 10 July 1967 Revision received: 10 June 1968 Published: 01 January 1969